A ROBUST PRACTICAL GENERALIZED PREDICTIVE CONTROL FOR BOILER SUPER HEATER TEMPERATURE CONTROL - Mohialdeen, Zaki Maki (Iraqi Journal for Electrical and Electronic Engineering, 2010)
A practical method of robust generalized predictive controller (GPC) application is developed using a combination of Ziegler-Nichols type functions relating the GPC controller parameters to a first order with time delay process parameters and a model matching controller. The GPC controller and the model matching controller are used in a master/slave configuration, with the GPC as the master controller and the model matching controller as the slave controller. The model matching controller parameters are selected to obtain the desired overall performance. The effectiveness of the proposed control method is tested by simulation using a mathematical model of the boiler super heater temperature process.